2007
DOI: 10.1371/journal.pgen.0030029
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Evaluation of Candidate Genes Identifies Associations between VEGF Polymorphisms and Bladder Cancer Risk

Abstract: Common genetic variation could alter the risk for developing bladder cancer. We conducted a large-scale evaluation of single nucleotide polymorphisms (SNPs) in candidate genes for cancer to identify common variants that influence bladder cancer risk. An Illumina GoldenGate assay was used to genotype 1,433 SNPs within or near 386 genes in 1,086 cases and 1,033 controls in Spain. The most significant finding was in the 5′ UTR of VEGF (rs25648, p for likelihood ratio test, 2 degrees of freedom = 1 × 10−5). To fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 19 publications
4
112
1
1
Order By: Relevance
“…The studies of Garcia-Closas et al and Shen et al revealed an association between the risk of cancer and a single XPC polymorphism, namely: between 33512C and the risk of bladder cancer, as well as the PAT+ polymorphism in intron 9 and the risk of squamous cell carcinoma of head and neck [55,56]. However, taking into account the high LD between these XPC variants, it remains to be determined whether a single polymorphism or their association is of most importance in the modulation of cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Garcia-Closas et al and Shen et al revealed an association between the risk of cancer and a single XPC polymorphism, namely: between 33512C and the risk of bladder cancer, as well as the PAT+ polymorphism in intron 9 and the risk of squamous cell carcinoma of head and neck [55,56]. However, taking into account the high LD between these XPC variants, it remains to be determined whether a single polymorphism or their association is of most importance in the modulation of cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Median number of treatment cycles administered was 7 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Dose reduction (>25% of the planned dose for any of the drug for two or more cycles) or treatment delay (>1 week of delay for two or more cycles) was necessary in eight patients (20%).…”
Section: Patients' Characteristics and Treatment Deliverymentioning
confidence: 99%
“…Previous studies have demonstrated that the presence of VEGF single nucleotide polymorphisms (SNPs) in the promoter and 5' untranslated region (UTR) regions may be a risk factor for prostate and bladder cancer development [9,10]. Moreover, VEGF SNPs may have a prognostic value for non-small cell lung, colorectal, ovarian, and breast cancer patients [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…An Illumina GoldenGate assay (Illumina, San Diego, CA, USA) was used to genotype the CDA polymorphism. 9,10 This technology has a concordance, reproducibility and call rate 499.5%. CDA Lys 27 Gln polymorphism genotyping has three potential results: most frequent homozygous (homozygote wild-type reference, Lys/Lys), heterozygous (Lys/Gln) and least common homozygous (homozgote variant, Gln/Gln).…”
Section: Rtog 9704mentioning
confidence: 99%